A Review of Longitudinal Research in the Product Innovation Field, with Discussion of Utility and Conduct of Sequence Analysis. Issue 6 (27th June 2013) - Perks, Helen; Roberts, Deborah
<x xml:space="preserve">Abstract</x> This paper examines how longitudinality is investigated in innovation research. A review of longitudinal methods in innovation articles, published between 2000 and 2011, is undertaken. Our findings show that longitudinal approaches to data collection are gaining some credence, in line with increased criticism of the overuse of positivist methods to study process‐based phenomena. However, results demonstrate a dearth of systematic longitudinal analytical methods employed in product innovation research. Static analytical methods are prominent. These inevitably lead to static presentation of results, and this is borne out in our findings. Second, the paper discusses the conduct and utility of a specific technique for product innovation research: sequence analysis. By drawing on two studies, which apply sequence analysis in product innovation research, sequence analysis is shown to be a useful technique to achieve rigor in analyzing longitudinal data. The paper concludes by discussing how such systematic methods for analyzing longitudinality in the innovation field demand greater usage and exploration.